2016
DOI: 10.1515/amm-2016-0295
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Selected Parameters of Organic-Inorganic Hybrid Membranes Based on Various Polymers and Nd-Fe-B Fillers

Abstract: In this paper magnetic organic-inorganic hybrid membranes based on EC, PPO polymer matrices and various magnetic powder microparticles were synthesized and studied. Constant pressure permeation technique and the Time Lag method were used to obtain the gas transport coefficients. The mechanical, rheological and magnetic parameters of magnetic hybrid membranes were examined. It was found that their separation and gas transport properties (D, P, S and α) were improved with the decrease in powder particle size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Membranes with magnetic properties have been used to separate oxygen/nitrogen [13][14][15][16][17][18][19][20], carbon dioxide/nitrogen [21][22][23][24], helium/carbon dioxide [25] and carbon dioxide/methane mixtures [23,26]. The magnetic properties of membrane filler and/or additionally applied an external magnetic field impact the separation of gaseous mixtures due to the different magnetic properties of their components as shown in Figure 1.…”
Section: Gas Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes with magnetic properties have been used to separate oxygen/nitrogen [13][14][15][16][17][18][19][20], carbon dioxide/nitrogen [21][22][23][24], helium/carbon dioxide [25] and carbon dioxide/methane mixtures [23,26]. The magnetic properties of membrane filler and/or additionally applied an external magnetic field impact the separation of gaseous mixtures due to the different magnetic properties of their components as shown in Figure 1.…”
Section: Gas Separationmentioning
confidence: 99%
“…Raveshiyan et al [9] observed the highest saturation magnetisation value (23 em•g −1 ) for a polysulfone (PSf) membrane modified with 10 wt% carbonyl iron powder. On the other hand, hard magnets have a high coercivity, which makes it difficult to magnetise and demagnetise them [14,17,18,30,33,34]. For this reason, placing the membranes loaded with hard magnets in an external magnetic field is unnecessary to obtain advantageous separation results.…”
Section: Gas Separationmentioning
confidence: 99%
“…Additionally, the membranes must be stable and adapted to the conditions of the fuel combustion process. Therefore, the authors proposed using hybrid membranes, also called mixed matrix membranes (MMMs) [94][95][96]. Hybrid membranes allow us to take advantage of a polymer matrix and inorganic additives.…”
Section: Clean Coal Technologies (Cct)mentioning
confidence: 99%
“…There are few scientific reports about O 2 /N 2 separation using magnetic MMMs, which demonstrate that the incorporation of magnetic particles into the membrane matrix improved its separation performance [22,[25][26][27][28][29][30][31][32][33][34]. With respect to the results published by Rybak research group, praseodymium and neodymium incorporation successfully enhanced the O 2 /N 2 separation performance of polymeric membranes like ethyl cellulose (EC), poly(2,6-dimethyl-1,4-phenylene oxide) (PPO), and linear polyimide (LPI) or hyperbranched polyimide (HBPI) [27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of magnetic membrane separation is affected by the magnetic property and size of the particles and the intensity of interactions between the gas molecules and magnetic channels. In several studies accomplished by the Rybak research group 25–31, 33, 35, magnetic MMMs were fabricated from praseodymium and neodymium magnetic particles. They investigated the particle size effect on the O 2 /N 2 separation; however, they did not study the effects of dispersion and arrangement of magnetic particles on the structure and magnetic properties of magnetic MMMs.…”
Section: Introductionmentioning
confidence: 99%